Research papers : the 12th international Arab conference on information technology : ACIT 2011 2026-02-15T17:00:32+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (Naif Arab University for Security Sciences, 2011)

(untitled)
"The papers represented reflect the distinctive contributions of multiple intelligentsia -- researchers, engineers, technical professionals and academicians. Together, they represent both government and non-government organizations -- research and academic. The present publication is a pioneer work on Information Technology."--Foreword